Dynamics of early post‐operative plasma ddcfDNA levels in kidney transplantation: a single‐center pilot study. (2nd October 2018) - Shen, Jia; Zhou, Yang; Chen, Yawen; Li, Xiaofeng; Lei, Wenhua; Ge, Jun; Peng, Wenhan; Wu, Jianyong; Liu, Guangjun; Yang, Gongda; Shi, Haifeng; Chen, Jianghua; et al.
Summary: Donor‐derived cell‐free DNA (ddcfDNA) is reported to be a promising noninvasive biomarker for acute rejection in organ transplant. However, studies on monitoring ddcfDNA dynamics during the early periods after organ transplantation are scarce. Our study assessed the dynamic variation in ddcfDNA in early period with various types and status of kidney transplantation. Target region capture sequencing used identifies ddcfDNA level in 21 kidney transplant recipients. Median ddcfDNA level was 20.69% at the initial time post‐transplant, and decreased to 5.22% on the first day and stayed at the stable level after the second day. The ddcfDNA level in DCD (deceased donors) group (44.99%) was significantly higher than that in LDRT (living donor) group (10.24%) at initial time, P < 0.01. DdcfDNA level in DGF (delayed graft function) recipients was lower (23.96%) than that in non‐DGF (47.74%) at the initial time, P = 0.89 (19.34% in DGF and 4.46% in non‐DGF on the first day, P = 0.17). DdcfDNA level at initial time significantly correlated with serum creatinine ( r 2 = 0.219, P = 0.032) and warm ischemia time ( r 2 = 0.204, P = 0.040). Plasma ddcfDNA level decreased rapidly follow an L‐shaped curve post‐transplant, and level in DGF declined slower than non‐DGF. The rebound of ddcfDNA level may indicate the occurrence of acute rejection.